ANALYSIS THE EFFECT OF ORGANIZATIONAL COMMITMENT ISLAMIC WORK ETHICS AND ORGANIZATIONAL CULTURE ON LECTURER PERFORMANCE AT STIE MANDALA - Tamriatin Hidayah; Hary Sulaksono (STIE Mandala Jember, 2022)
This study aims to see the effect of organizational commitment variables, Islamic work ethicsand organizational culture on the performance of lecturers at STIE Mandala. The method ofcollecting data is through a questionnaire. The sampling method used a saturated sample. Thedata analysis method used is Multiple Linear Regression. The results obtained from this studyare organizational commitment has no significant influence on employee performance, Islamicwork ethics and organizational culture have a significant effect on lecturer performance at STIEMandala. The implications that can be formulated related to the results of this study are that theleadership of higher education institutions should strive to increase the organizationalcommitment of their employees, create an organizational culture that is able to create a goodwork culture.